The Feldstein-Horioka paradox: A selective survey of the literature - Susanne Lapp (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
The paper provides a selective survey of the literature on the Feldstein-Horioka paradox. The observed high correlation between national savings and domestic investment emerges as a robust empirical regularity. If this regularity is to be attributed to low capital mobility (due to government interventions or market imperfections) or other factors (such as immobility of goods, shocks or intertemporal budget constraints) cannot be resolved. The empirical evidence on the relative importance of the possible factors is too sketchy. Excluding government interventions, the possible impact of market imperfections in causing saving-investment corrrelations has hardly been investigated so far.
Keywords: E44; F21; F32; 330; Kapitalmobilität; Sparen; Investition; Marktversagen; Welt; Theorie